PERFORMANCE OF MALE BALINESE DUCKS FED DRAGON FRUIT PEEL JUICE (Hylocereus polyrhizus) THROUGH DRINKING WATER - N. P., Erlina; Siti, N. W.; Wibawa, A. A. P. P. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the effect of the performance of male Balinese ducks given dragon fruit peel juice through drinking water. The research was conducted at the Farm of the Jl. Br. Tengah Gulingan, Kabupaten Badung, Bali from August to October 2023. The design used was a completely randomized design (CRD) with 4 treatments and 5 replicates. Each cage plot was filled with 3 DOD Balinese ducks with an average body weight of 45,37g ± 9,07g so that the number of Balinese ducks used was 60. The four treatments were male Balinese ducks given drinking water without dragon fruit peel extract (P0), drinking water with dragon fruit peel extract as much as 6% (P1), 8% (P2) and 10% (P3). The variables observed were initial body weight, final body weight, body weight gain, ration consumption, drinking water consumption, and Feed Convertion Ratio (FCR). The results showed that P3 had a significant effect (P < 0.05) on the variables of final body weight, body weight gain, ration consumption and drinking water consumption which were statistically different (P < 0.05). Based on the results of this study it can be concluded that giving 10% dragon fruit peel juice through drinking water can improve the performance of male Balinese ducks.